2019
DOI: 10.1039/c9md00102f
|View full text |Cite
|
Sign up to set email alerts
|

Binding site characterization – similarity, promiscuity, and druggability

Abstract: Promiscuity as key to drug repurposing, off-target prediction, polypharmacology: What can be learned based on the comparison of binding sites and the description of their properties? Herein, we discuss binding site similarities with a special focus on medicinal chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 69 publications
4
38
0
1
Order By: Relevance
“…The fundamental principle of drug discovery is that biologically active ligands are complimentary in molecular features and shape to the receptor. These can include physiochemical properties such as hydrophobicity, size, as well as the enclosure of the binding pocket and its promiscuity 33,34 . A strictly predominantly hydrophobic pocket might indicate a promiscuous binding site that may accommodate a wide-varying of ligands in different modes, some hydrophobic patches are still nevertheless ideal for ligand design.…”
Section: Resultsmentioning
confidence: 99%
“…The fundamental principle of drug discovery is that biologically active ligands are complimentary in molecular features and shape to the receptor. These can include physiochemical properties such as hydrophobicity, size, as well as the enclosure of the binding pocket and its promiscuity 33,34 . A strictly predominantly hydrophobic pocket might indicate a promiscuous binding site that may accommodate a wide-varying of ligands in different modes, some hydrophobic patches are still nevertheless ideal for ligand design.…”
Section: Resultsmentioning
confidence: 99%
“…Pockets with a DGSS druggability score ≥ 0.4 were considered druggable [96] . The druggability threshold was previously defined by Volkamer and the methodology was applied with success by other authors [90] , [96] , [98] , [99] , [100] .…”
Section: Methodsmentioning
confidence: 99%
“…At the structural level, promiscuity can be viewed from a ligand [17,18] or target perspective [17,20], which is not mutually exclusive. Several studies have revealed that promiscuous ligands often bind to similar binding sites in proteins [17,21,22]. If proteins belong to the same family they typically have similar binding sites (and functions), which favor compound binding to related targets.…”
Section: Structure-based Exploration Of Multitarget Activitymentioning
confidence: 99%